Read from Local to Global: A Culture-based Reading Material - Fu, Wei (Advances in Social Sciences Research Journal, 2018)
Chinese language has risen to become the world popular language among the foreign language learners. According to the recent data, 516 Confucius Institutes and 1076 Confucius Classroom established all over the world, with more than 100 million foreign students enrolled, especially 48 Confucius Institutes are distributing in 33 Africa countries, to provide the scope for people to learn Chinese language and culture. This paper is based on the previous experts’ call that teaching language in 21st century needs to be involved with cultural awareness in concerning both regional and global societies, in order to enhance learners’ the fifth skill of the language learning. This paper aims to use the local culture to facilitate a reading content to promote students’ Chinese communication skills. The use of local culture contents is one of the effective ways to stimulate students’ motivation in language class. Under the guidance of Chinese Language Proficiency Scales for Speakers of Other Language and International Curriculum for Chinese Language Education, 12 units of Ethiopian cultures, landscapes, beliefs, customs, arts and festivals that were incorporated in the reading materials are identified. The demonstration samples of the model units will be shown so as to culturally value reading materials to any other Chinese language learners. This new orchestrated material will undoubtedly can encourage learners to gain a deeper understanding of their own culture and to share these insights in Chinese to any others as well as more effectively in learning a global language. Moreover, this material also can enlighten an idea to apply to some other reading contexts for Africa countries.